Technology-Enhanced Inclusive Education and Digital Child Protection for Violence Prevention in Schools - Yati Yati; Fitra Jaya; Kadarisman Kadarisman; Romi Siswanto; Sucipto Sucipto (LP. Ma'arif Janggan Magetan, 2026)
This paper proposes a technological approach to stopping violence in educational settings by integrating education and digital child protection. We conducted a qualitative, systematic literature review of national and international databases and analyzed policy recommendations regarding UNESCO, UNICEF, WHO, and the Indonesian Regulation No. 46/2023. The inclusion criteria included 20 peer-reviewed articles published between 2000 and 2025. We coded the types of violence, technology functions, roles of users and implementation contexts using content analysis. Three barriers are identified by the findings, including low educator competence in inclusive pedagogy and positive discipline, poor child- and disability-friendly facilities, and stigma of diversity that carries over into virtual communications. Reliant on these trends, the suggested model incorporates three domains. First, SOPs, privacy standards, and role-based workflow that connect reporting to accountable response and the protection of confidentiality are determined by digital safeguarding governance. Second, inclusive learning is enhanced by technology guaranteeing digital access, inculcation of digital citizenship and character values, and routines of safe interactions across platforms. Third, digital protection systems offer confidential or anonymous reporting, case-documentation, referral to counseling services and school-climate monitoring as an early warning.